General, organic, and biochemistry - Denniston, Katherine J.; Topping,Joseph.J ([S.l.] : Mcgraw-Hill College, 2000)
The fifth edition of General, Organic, and Biochemistry is designed to help undergraduate health-related majors, and students of all other majors, understand key concepts and appreciate the significant connections between chemistry, health, disease, and the treatment of disease. This text continues to strike a balance between theoretical and practical chemistry, while emphasizing material that is unique to health-related studies. Designed for the one- or two-semester course, the text has an easy-to-follow problem-solving pedagogy, vivid illustrations, and engaging applications. The updating of the art program throughout, along with many new questions, problems, and discussion topics, continues to make this book appealing to students and instructors alike.